Модификации русских слов при создании молодежного сленга в романе Энтони Берджессa „Заводной апельсин” - Dominika Wesołek (Studia Rossica Posnaniensia)
The article presents an attempt at analyzing the teen slang that Anthony Burgess used in his novel A Clockwork Orange. This slang is mainly based on words that have been borrowed from Russian. This article discusses different ways of introducing Russian words into the English language system.